Infection Control Initiative: Epidemiology & what we can do? - Omar, Naureen; Batool, Sadia; Thaver, Inayat H. (Infectious Diseases Journal of Pakistan, 2023)
Background: Hospital acquired infections occur due to cross infection from one patient to another or by doctors, nurses or other hospital staff, and should be addressed in addition to offering optimal healthcare and treatment measures. All hospitals should ensure basic infection control mechanisms which are the key to control infections. A study was conducted in a private tertiary care set up to assess the infection control status and observance of protocols with the aim to conduct critical self appraisal to improve healthcare services. Material and Methods: A structured questionnaire based on the standards used by Government of Pakistan was adapted and data was collected by the faculty members. Non-probability sampling technique with focus on major departments of the hospital having higher patient loads were used.The data was collected by direct observation, checking of records and interviews as needed from the Emergency Unit, Operation theatre, Wards (Medical, Surgical, and Gynaecology& Obstetrics) and Outdoor Unit, Labour room, ICU (Adult & Paediatrics) and Nursery. Data was compiled and analysed using SPSS version 17. Microsoft Excel was used for graphic presentation. Study was conducted from February 2015 to March 2015. Results: It was observed that basic infection control measures were available, Anti disinfectants (69%), Sterilized equipment (67%) and clean supplies (94%). Precautionary measures were being ensured in major areas such as, prevention of bloodstream infections (74%), perinatal precautions (78%) and prevention of UTI (55%). Hand hygiene practices were promoted(79%), however the waste disposal (18%) was at sub-par level. Inadequacy of water supply (32%) was also observed. Compliances were based on interviews taken and observations done then recorded in the questionnaire, in all the areas visited by the investigators. Conclusion: Our study concluded that the infection control measures are being followed in an adequate manner, with no gross deficiencies; however, it identified some areas for further improvements like waste disposal mechanisms and adequacy of water supply.